RELEVANSI KONSEP PENDIDIKAN HUMANIS-RELIGIUS ABDURRAHMAN MAS’UD DENGAN PENGUATAN PENDIDIKAN KARAKTER DAN KETERAMPILAN PESERTA DIDIK ABAD 21 - Zeni Murtafiati Mizani (Universitas Islam Sultan Agung, 2021)
The purpose of this study was to: explain the concept of Humanist-religious education Abdurrahman Mas'ud; describe the concept of strengthening character education; detail the skills of the 21st-century students; Analyze the relevance of humanist education with the strengthening of 21-century character education. Data was obtained through literature studies on books written by Abdurrahman Mas'ud and then analyzed critically and in-depth. The results of this study indicate that the objectives of Humanism-Religious Education Abdurrahman Mas'ud are the development of human potential as religious beings and social beings by offering six aspects of education development. In line with the strengthening of the 21st-century character, education consists of five main values, namely religion, nationalism, independence, cooperation, and integrity. The skills of 21st-century students are critical thinking skills, creativity, communication, and collaboration. The relevance of the concept of humanist education Religious Abdurrahman Mas'ud with strengthening character education lies in the goals of religious humanist education. While the relevance of the concept of humanist education Religious Abdurrahman Mas'ud with the skills of the 21st-century students lies in six aspects of the development of Abdurrahman Mas'ud character education.Keywords: Religious Humanist Education, Strengthening Character Education, Student Skills